(untitled) (Acta Scientiarum. Language and Culture, 2021)
This article analyses the olfactory landscapes represented in the novel Não se pode morar nos olhos de um gato (You can’t live in a cat’s eyes) by Ana Margarida de Carvalho (2016) reflecting upon the way in which the various smells described ‘presentify’ the multiple memories of the characters, emphasising their human dimension in a confinement scenario predisposed to completely dehumanising them. Using the theoretical contributions of Drobnick (2006a, 2006b), Reinarz (2014) and Byung-Chul Han (2015) among others, we examine how the smellscapes contribute to the construction of the characters’ identitary memory giving the narrative temporal cohesion.